Island-shaped MS2at-TiO2 heterojunction and preparation method and application thereof

By constructing an island-like MS2@TiO2 heterojunction and using its built-in electric field to achieve rapid adsorption and catalytic conversion of polysulfides, the problem of low cycling durability of lithium-sulfur batteries is solved, and the cycle stability and electrochemical performance of the battery are significantly improved.

CN119683695AActive Publication Date: 2025-03-25ZHONGBEI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411961033.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-25
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing lithium-sulfur batteries have low cycling durability due to the shuttle effect of lithium polysulfide, making it difficult to effectively inhibit the dissolution and shuttle of polysulfide, which limits their practical application.

Method used

By constructing an island-like MS2@TiO2 heterojunction, the adsorption capacity of TiO2 and the catalytic action of MS2 are used to form a built-in electric field to achieve rapid adsorption and catalytic conversion of polysulfides, thereby improving the cycle stability of lithium-sulfur batteries.

Benefits of technology

The rapid adsorption and catalytic conversion of polysulfides have been achieved, which significantly improves the cycle stability and electrochemical performance of lithium-sulfur batteries, including high initial discharge capacity, good rate performance and long-term cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683695A_ABST
    Figure CN119683695A_ABST
Patent Text Reader

Abstract

The invention particularly relates to an islanding-shaped MS2at-TiO2 heterojunction as well as a preparation method and application of the islanding-shaped MS2at-TiO2 heterojunction. The preparation method comprises the following steps: firstly, preparing an islanding-shaped MS2-coated TiO2 (M = Fe, Co, Ni or Cu) heterojunction consisting of MS2 nanoparticles and TiO2 nanobelts through simple hydrothermal, ion exchange and sulfuration reactions so as to capture and catalyze polysulfides, and uniformly anchoring the MS2 nanoparticles on the surfaces of the TiO2 nanobelts; in the MS2 (at) TiO2 heterojunction, TiO2 is used as an adsorption site to effectively inhibit shuttling of lithium polysulfide, and MS2 is used as an electro-catalysis site to improve conversion kinetics of the lithium polysulfide. The Li-S battery adopting the MS2-coated TiO2 heterojunction modified diaphragm shows excellent electrochemical performance, including the high initial discharge capacity of 2318 mAh g <-1 > at 0.1 C, the capacity fading rate of 0.046% at 1 C and excellent long-term cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery materials, and in particular to an island-shaped MS2@TiO2 heterojunction and a preparation method and application thereof. Background Art

[0002] Due to its abundant reserves, environmental friendliness, and large theoretical specific capacity (1675 mAh g -1 ), energy density up to 2500 Whkg -1 Lithium-sulfur batteries are considered to be a promising energy storage device. Despite these advantages, their practical applications are greatly limited by their low cycle durability caused by the dissolution and shuttle effect of lithium polysulfides (LiPSs). Therefore, inhibiting the shuttle effect of polysulfides and improving the performance of lithium-sulfur batteries are current research hotspots.

[0003] To address the shuttling effect of polysulfides, the commonly used methods currently include designing sulfur host materials, including chemical adsorption strategies (using polar materials such as transition metal compounds, covalent organic frameworks, metal organic frameworks, and MXenes) and physical confinement methods (using nanocarbon materials with various innovative structures). However, limited adsorption sites and sulfur storage space can lead to structural collapse of the host material. Another effective strategy to inhibit the dissolution / shuttling of LiPSs is to establish a shuttle barrier between the cathode and the anode, that is, to modify the diaphragm. The materials commonly used to modify the diaphragm are: carbon materials and transition metal compounds (oxides, sulfides, phosphides, nitrides, etc.). The physical confinement of non-polar carbon materials is very limited in adsorbing large amounts of polysulfides. In contrast, polar materials such as transition metal oxides such as TiO2 have stronger adsorption capacity for LiPSs. Although some electrocatalytic materials (such as FeS2, CoS2, Ni2P, and ZnS) can accelerate the conversion of soluble LiPSs to Li2S, they usually have poor conductivity. It is a challenge for a single functional material to simultaneously meet multiple requirements, including high conductivity, strong adsorption capacity, and excellent electrocatalysis for LiPSs.

[0004] Since heterojunctions have different interfaces, strong structures and synergistic effects, they usually have higher conductivity, and the charge redistribution in the heterostructure will induce more active sites for energy storage, thereby achieving continuous adsorption and conversion, higher reversible capacity and better cycle stability. Therefore, it is important to develop heterojunctions with low development cost, simple process, and rapid adsorption and catalytic conversion of polysulfides for lithium-sulfur batteries. Summary of the invention

[0005] The present invention overcomes the shortcomings of the prior art and aims to solve the technical problem of providing an island-shaped MS2@TiO2 heterojunction with low cost, simple process, and rapid polysulfide adsorption and catalytic conversion. From the perspective of heterojunction construction, based on the needs of enhancing the built-in electric field strength and improving cycle stability, TiO2 with a wide energy band structure and adsorption effect on polysulfides and metal sulfide MS2 (M=Fe, Co, Ni, Cu) with catalytic effect are selected to construct the heterojunction, inducing the formation of a built-in electric field, and realizing the continuous process of polysulfide adsorption, anchoring and catalytic conversion, thereby improving the cycle stability of lithium-sulfur batteries.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing an island-shaped MS2@TiO2 heterojunction, comprising the following steps: (1) Preparation of precursor Na2Ti2O5: Disperse titanium powder in NaOH solution, mix thoroughly and pour into a reactor for hydrothermal reaction; filter, wash and dry to obtain precursor Na2Ti2O5; (2) Ion exchange reaction: adding a dry Na2Ti2O5 precursor to a salt solution of a metal M, stirring the solution under magnetic stirring and leaving the solution to stand for 2 to 6 hours to allow the ion exchange reaction to proceed fully; filtering, washing and drying the solution; the metal M is at least one of Fe, Co, Ni and Cu; (3) Sulfidation reaction: The dried sample after ion exchange and sulfur powder are placed in a tubular furnace for sulfurization calcination treatment. After cooling, an isolated MS2@TiO2 heterojunction is obtained.

[0007] As a further limitation of the technical solution of the present invention, the temperature of the hydrothermal reaction in step (1) is 160-200°C for 24-60 h.

[0008] As a further limitation of the technical solution of the present invention, the molar ratio of the titanium powder to the NaOH solution in step (1) is 1:10 to 1:20.

[0009] As a further limitation of the technical solution of the present invention, in step (2), the metal M salt is at least one of ferric nitrate, cobalt nitrate, nickel nitrate, copper nitrate, ferric chloride, cobalt chloride, nickel chloride and copper chloride; the molar ratio of the metal M salt to the Na2Ti2O5 precursor is 5-10:1; the concentration of the metal M salt solution is 0.25 mol L -1 .

[0010] As a further limitation of the technical solution of the present invention, in step (3), the mass ratio of the dried sample to the sulfur powder is 1:3-6.

[0011] As a further limitation of the technical solution of the present invention, the calcination parameters in the tube furnace of step (3) are: heating to 400-600° C. under an inert atmosphere, maintaining for 2-4 h, and then naturally cooling to room temperature.

[0012] First, an island-like MS2@TiO2 (M=Fe, Co, Ni, Cu) heterojunction consisting of MS2 (M=Fe, Co, Ni, Cu) nanoparticles and TiO2 nanobelts was prepared by simple hydrothermal, ion exchange and sulfurization reactions to capture and catalyze polysulfides, in which MS2 nanoparticles were uniformly anchored on the surface of TiO2 nanobelts. In the MS2@TiO2 (M=Fe, Co, Ni, Cu) heterojunction, TiO2 as an adsorption site can effectively inhibit the shuttling of lithium polysulfides, while MS2 as an electrocatalytic site can improve the conversion kinetics of polysulfides.

[0013] The present invention also provides an island-shaped MS2@TiO2 heterojunction obtained by the above-mentioned preparation method.

[0014] In addition, the present invention also provides the use of the isolated island-shaped MS2@TiO2 heterojunction obtained by the above preparation method in modifying the lithium-sulfur battery separator and improving the electrochemical performance of the battery.

[0015] As a further limitation of the technical solution of the present invention, the method of using an island-shaped MS2@TiO2 heterojunction to modify a lithium-sulfur battery separator is as follows: the MS2@TiO2 active material, the conductive agent and the binder are respectively weighed in a mass ratio of 6 to 8:3 to 1:1, the mixture is ground and added to a solvent to obtain a slurry, which is coated on the surface of the separator and vacuum dried to obtain a MS2@TiO2 modified separator.

[0016] As a further limitation of the technical solution of the present invention, the conductive agent is at least one of conductive carbon black, acetylene black, Ketjen black and graphene; the binder is polyvinylidene fluoride; and the solvent is N-methylpyrrolidone.

[0017] Due to the different energy band gaps of MS2 and TiO2, the heterojunction interface of these two components generates a built-in electric field, which accelerates the conversion of polysulfides (especially the reduction of Li2S2 to Li2S). In addition, Li-S batteries using MS2@TiO2 (M=Fe, Co, Ni, Cu) heterojunction modified separators exhibit excellent electrochemical performance, including 2318 mAh g at 0.1 C. -1 The high initial discharge capacity, low capacity decay rate of 0.046% at 1 C and excellent long-term cycle stability are also shown.

[0018] Compared with the prior art, the present invention has the following beneficial effects: The present invention utilizes cheap and readily available raw materials to prepare, through simple hydrothermal reaction, ion exchange and sulfurization reaction, an island-shaped MS2@TiO2 (M=Fe, Co, Ni, Cu) heterojunction having excellent adsorption properties, efficient catalytic conversion properties, and outstanding electrochemical performance, providing a new method for preparing lithium-sulfur battery separator modification materials having both excellent adsorption properties and rapid catalytic conversion properties.

[0019] The isolated MS2@TiO2 (M=Fe, Co, Ni, Cu) heterojunction prepared by the present invention not only has the ability to quickly adsorb lithium polysulfide, but also can significantly inhibit the penetration of polysulfide when coated on a commercial PP separator with a thickness of only 8 μm, and only slightly changes color after 8 hours. When the battery is assembled with the modified separator, it can achieve extremely high initial capacity, good rate performance and cycle stability.

[0020] The isolated island-shaped MS2@TiO2 (M=Fe, Co, Ni, Cu) heterojunction prepared by the present invention has low cost, simple steps and can be industrialized. This isolated island-shaped heterojunction construction project can reduce the shuttle effect and promote the catalytic conversion of polysulfides, providing important inspiration for improving the electrochemical performance of lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 These are the SEM image and mapping image of the precursor Na2Ti2O5 prepared in Example 1 of the present invention.

[0022] Figure 2 These are the SEM, TEM, SAED and Mapping images of FeS2@TiO2 prepared in Example 1 of the present invention.

[0023] Figure 3 XRD diagrams of FeS2@TiO2 and TiO2 prepared in Example 1 of the present invention and Comparative Example 1.

[0024] Figure 4 These are the SEM and Mapping images of TiO2 prepared in Comparative Example 1 of the present invention.

[0025] Figure 5 Pictures of FeS2@TiO2 / PP (right) and PP (left) coated in Example 5 of the present invention.

[0026] Figure 6 This is a comparison chart of the permeation experiments of Li2S6 on FeS2@TiO2 / PP, TiO2 / PP and PP membranes prepared in Example 1 of the present invention and Comparative Example 1.

[0027] Figure 7This is a cycle performance diagram of the FeS2@TiO2 / PP, TiO2 / PP and PP separator assembled batteries prepared in Example 1 of the present invention and Comparative Example 1.

[0028] Figure 8 This is the rate diagram of the FeS2@TiO2 / PP, TiO2 / PP and PP separators prepared in Example 1 of the present invention and Comparative Example 1 after assembling the battery. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific embodiments. Example 1

[0030] A method for preparing an island-shaped FeS2@TiO2 heterojunction (1) Disperse titanium powder (1 g) in 80 mL of 5 mol L -1 After being fully mixed, the solution was poured into a 100 mL high pressure reactor and reacted by hydrothermal method at 180 °C for 24 hours. After cooling to room temperature, the precipitate was collected by filtration and washed with distilled water and ethanol three times respectively. Finally, the precursor Na2Ti2O5 was obtained by drying at 60 °C; the corresponding SEM images are shown in Figure 1 shown.

[0031] (2) In 30 mL of 0.25 mol L -1 0.2 g of dried Na2Ti2O5 precursor was added to the Fe(NO3)3 solution, and the mixture was stirred for 30 min and then allowed to stand for 2 h to allow the ion exchange reaction to proceed fully. After the reaction, the mixture was filtered and washed three times with deionized water and ethanol, and then dried at 60 °C. (3) The dried sample and sulfur powder after ion exchange were placed in a tube furnace for sulfurization treatment and reacted in an argon environment at 500°C for 2 h. After cooling to room temperature, the FeS2@TiO2 heterojunction material was obtained. The corresponding SEM images are shown in Figure 2. Figure 2 . XRD pattern Figure 3 shown. Example 2

[0032] A method for preparing an island-shaped CoS2@TiO2 heterojunction: (1) Na2Ti2O5 was synthesized according to step (1) of Example 1; (2) In 30 mL of 0.25 mol L -1 0.2 g of dried Na2Ti2O5 precursor was added to the Co(NO3)2 solution, and the mixture was stirred for 30 min and then allowed to stand for 2 h to allow the ion exchange reaction to proceed fully. After the reaction, the mixture was filtered and washed three times with deionized water and ethanol, and then dried at 60 °C. (3) The dried sample and sulfur powder after ion exchange were placed in a tube furnace for sulfurization treatment and reacted at 500 °C in an argon environment for 2 h. After cooling to room temperature, the CoS2@TiO2 heterojunction material was obtained. Example 3

[0033] A method for preparing an island-shaped NiS2@TiO2 heterojunction: (1) Na2Ti2O5 was synthesized according to step (1) of Example 1; (2) In 30 mL of 0.25 mol L -1 0.2 g of dried Na2Ti2O5 precursor was added to the Ni(NO3)2 solution, and the mixture was stirred for 30 min and then allowed to stand for 2 h to allow the ion exchange reaction to proceed fully. After the reaction, the mixture was filtered and washed three times with deionized water and ethanol, and then dried at 60 °C. (3) The dried sample and sulfur powder after ion exchange were placed in a tube furnace for sulfurization treatment and reacted in an argon environment at 500°C for 2 h. After cooling to room temperature, the NiS2@TiO2 heterojunction material was obtained. Example 4

[0034] A method for preparing an island-shaped CuS2@TiO2 heterojunction: (1) Na2Ti2O5 was synthesized according to step (1) of Example 1; (2) In 30 mL of 0.25 mol L -1 0.2 g of dried Na2Ti2O5 precursor was added to the Cu(NO3)2 solution, and the mixture was stirred for 30 min and then allowed to stand for 2 h to allow the ion exchange reaction to proceed fully. After the reaction, the mixture was filtered and washed three times with deionized water and ethanol, and then dried at 60 °C. (3) The dried sample and sulfur powder after ion exchange were placed in a tube furnace for sulfurization treatment and reacted at 500 °C in an argon environment for 2 h. After cooling to room temperature, the CuS2@TiO2 heterojunction material was obtained.

[0035] Comparative Example 1 Preparation method of TiO2: The difference from the above embodiment 1 is that: The solution for the ion exchange reaction is HCl, followed by direct calcination without adding sulfur powder during the calcination process; (1) Na2Ti2O5 was synthesized according to step (1) of Example 1; (2) In 1 mol L -10.2 g of dried Na2Ti2O5 precursor was added to the HCl solution, magnetically stirred for 30 min and then allowed to stand for 2 h. After the reaction, the sample was filtered and washed three times with deionized water and ethanol, and then dried at 60 °C; (3) The dried sample after ion exchange was placed in a tube furnace, reacted at 500 °C in an argon environment for 2 h, and then cooled to room temperature to obtain TiO2.

[0036] The SEM image of TiO2 prepared in this comparative example is shown in the attached Figure 4 As shown, it shows a flower-like nanoribbon structure with no particles attached to it.

[0037] The island-shaped FeS2@TiO2, CoS2@TiO2, NiS2@TiO2, CuS2@TiO2 and TiO2 prepared in Example 1, Example 2, Example 3, Example 4 and Comparative Example 1 of the present invention were used as diaphragm modification materials to conduct a visualization experiment on the adsorption of lithium polysulfide, and were assembled with lithium sheets and S / C positive electrodes into CR2025 button-type Li-S batteries for electrochemical performance tests: Li-S battery assembly: Step 1: Weigh the MS2@TiO2 heterojunction / TiO2 material, graphene, and polytetrafluoroethylene in a mass ratio of 8:1:1 and grind them evenly, transfer them to a 5 mL weighing bottle, then drop 2 mL of nitrogen methyl pyrrolidone, continue stirring for 4 h to form a slurry, apply it on the PP diaphragm, and then dry it in a vacuum oven at 60 °C for 12 h. Use a slicer to cut it into a 19 mm diameter disc composite diaphragm, marked as MS2@TiO2 / PP and TiO2 / PP respectively; Figure 5 .

[0038] Step 2: Li-S battery assembly process; the Li-S battery assembled with MS2@TiO2 / PP is marked as battery 1, and the Li-S battery assembled with TiO2 / PP is marked as battery 2; Lithium polysulfide adsorption visualization: In the H-type electrolytic cell, different diaphragms were used to test the diffusion of polysulfide. 67 mL of 0.02 M Li2S was added to the left side, and 7 mL of DOL:DME = 1:1 solution was added to the right side. Different diaphragms were used to sandwich the H device. Figure 6 The color of the left chamber with the original PP separator permeates to the right after 1 h, while only a slight color change is observed after 8 h with the FeS2@TiO2 modified separator, which confirms the excellent ability of the FeS2@TiO2 heterojunction to suppress polysulfide shuttling.

[0039] Battery performance evaluation: Battery 1 and Battery 2 were tested for cycle stability at current densities of 0.1 C and 1 C, and for rate performance at 0.1 C, 0.2 C, 0.5 C, 1.0 C, and 2.0 C. Figure 7 and Figure 8 At 0.1C, the initial capacity of the main sample is as high as 2318 mAh / g, while that of the comparative sample is 1937 and 905.2, and the battery has good reversibility.

[0040] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing an island-shaped MS2@TiO2 heterojunction, characterized in that: The following steps are involved: (1) Preparation of precursor Na2Ti2O5: Disperse titanium powder in NaOH solution, mix thoroughly and pour into a reactor for hydrothermal reaction; After filtering, washing and drying, the precursor Na2Ti2O5 is obtained; (2) Ion exchange reaction: adding a dry Na2Ti2O5 precursor to a salt solution of a metal M, stirring the solution under magnetic stirring and leaving the solution to stand for 2 to 6 hours to allow the ion exchange reaction to proceed fully; filtering, washing and drying the solution; the metal M is at least one of Fe, Co, Ni and Cu; (3) Sulfurization reaction: The dried sample after ion exchange and sulfur powder are placed in a tubular furnace for sulfurization calcination treatment. After cooling, an isolated MS2@TiO2 heterojunction is obtained.

2. The method for preparing an isolated island-shaped MS2@TiO2 heterojunction according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (1) is 160-200 °C for 24-60 h.

3. The method for preparing an isolated island-shaped MS2@TiO2 heterojunction according to claim 1, characterized in that: The molar ratio of the titanium powder to the NaOH solution in step (1) is 1:10 to 1:

20.

4. The method for preparing an isolated island-shaped MS2@TiO2 heterojunction according to claim 1, characterized in that: In step (2), the metal M salt is at least one of ferric nitrate, cobalt nitrate, nickel nitrate, copper nitrate, ferric chloride, cobalt chloride, nickel chloride and copper chloride; the molar ratio of the metal M salt to the Na2Ti2O5 precursor is 5-10:1; the concentration of the metal M salt solution is 0.25 mol / L -1 .

5. The method for preparing an isolated island-shaped MS2@TiO2 heterojunction according to claim 1, characterized in that: In step (3), the mass ratio of the dried sample to the sulfur powder is 1:3-6.

6. The method for preparing an isolated island-shaped MS2@TiO2 heterojunction according to claim 1, characterized in that: The calcination parameters in the tubular furnace of step (3) are as follows: heating to 400-600°C under an inert atmosphere, maintaining the temperature for 2-4 hours, and then naturally cooling to room temperature.

7. An island-shaped MS2@TiO2 heterojunction obtained according to the preparation method according to any one of claims 1 to 6.

8. Application of an island-shaped MS2@TiO2 heterojunction according to claim 7 in modifying lithium-sulfur battery separators and improving battery electrochemical performance.

9. The use according to claim 8, characterized in that: The method of using an island-shaped MS2@TiO2 heterojunction to modify a lithium-sulfur battery separator is as follows: MS2@TiO2 active material, conductive agent and binder are weighed respectively in a mass ratio of 6 to 8:3 to 1:1, and the slurry is prepared by grinding and adding into a solvent, which is coated on the separator surface, and the MS2@TiO2 modified separator is obtained after vacuum drying.

10. The use according to claim 9, characterized in that: The conductive agent is at least one of conductive carbon black, acetylene black, Ketjen black and graphene; the binder is polyvinylidene fluoride; and the solvent is N-methylpyrrolidone.

Citation Information

Patent Citations

  • Preparation method of metal nitride-metal oxide heterojunction modified diaphragm for lithium-sulfur battery and lithium-sulfur battery containing diaphragm

    CN111864156A

  • Preparation method of SnS2-SnO2 heterogeneous nano material and application of SnS2-SnO2 heterogeneous nano material in lithium-sulfur battery

    CN117954777A